A multidisciplinary program of preparation for childbirth and motherhood: maternal anxiety and perinatal outcomes - Prevedel Tânia TS; De Conti Marta HS; Consonni Marcos; Calderon Iracema MP; Consonni Elenice B; Rudge Marilza VC (BMC, 2010)
Abstract Background To study maternal anxiety and perinatal outcomes in pregnant women submitted to a Multidisciplinary Program for Childbirth and Motherhood Preparation (MPCM). Methods This is a not randomized controlled trial on 67 nulliparous pregnant women divided into two groups according to participation (MPCM Group; n = 38) or not (Control Group; n = 29) in MPCM. The program consisted of 10 meetings (between the 18th and the 38th gestational week) during which educational, physiotherapeutic and interaction activities were developed. Anxiety was quantified at the beginning and at the end of the gestational period by the Trace-State Anxiety Inventory (STAI). Results Initial maternal anxiety was equivalent between the groups. At the end of the gestational period, it was observed that anxiety levels increased in the Control Group and were maintained in the MPCM Group. A higher occurrence of vaginal deliveries (83.8%) and hospital discharge of three-day-older newborns (81.6%) as a result of MPCM was also significant. Levels of state-anxiety at the end of pregnancy showed a negative correlation with vaginal delivery, gestational age, birth weight and Apgar index at the first minute and positive correlation with the hospital period remaining of the newborns. Conclusion In the study conditions, MPCM was associated with lower levels of maternal anxiety, a larger number of vaginal deliveries and shorter hospitalization time of newborns. It was not related to adverse perinatal outcomes.